PENGELOLAAN PROGRAM SANITASI BERBASIS MASYARAKAT (SANIMAS) DI KELURAHAN MERANTI PANDAK KOTA PEKANBARU - Icha Octavia; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The background of this thesis is about Community-Based Sanitation Program Management in Meranti Pandak Village, Pekanbaru City. The purpose of this study was to determine the management of community-based sanitation program in the Meranti Pandak Village, Pekanbaru City. This study uses George Terry’s management theory in Sukarna (2011) which uses 4 indicators, namely: planning, organizing, actuating and controlling. The research method used is a qualitative research method with data collection techniques interviews, observation dan documentation. The results of this study indicate that the management of community-based sanitation program in the Meranti Pandak village, Pekanbaru city has not been well managed. This can be seen from the research results that there are several sub-indicators on the management concept that have not been fulfilled, namely the relationship/communication system in the actuating indicator and the implementation measure in the controlling indicator. The unfulfilled sub-indicators are caused by several factors, namely 1) community participation, lack of understanding and participation of the importance of sanitation in environmental health and 2) communication factors, lack of communication between the government and local communities so that sanitation management has not been well managed. Keywords: Management, Program, Sanitation.